Effect of Opening Size on Wind-Driven Cross Ventilation - Moey, Lip Kean; Sing, Yao Horng; Tai, Vin Cent; Go, Tze Fong; Sia, Yaw Yoong (International Journal of Integrated Engineering, 2021)
The opening size on indoor airflow is important to the ventilation of building because various size openings change the ventilation performance for building. Therefore, the objective of this study is to investigate the effect of opening size on indoor airflow characteristics of naturally ventilated building model. The numerical simulation with steady RANS equations was used. A total of six different opening ratios, namely 4:1, 2:1, 1:1, 1:2, 4:9 and 1:4 were considered in this study. The results of mesh independence study and model validation were also in good agreement with previous study. The simulation results show that velocity and pressure of the indoor air, ventilation rate, and pressure coefficient are highly dependent on the opening ratio. The velocity and pressure contour indicate that the lower the opening ratio, the higher the velocity and subsequently lower pressure inside the building. In addition, the pressure coefficient and ventilation rate are also increased as the opening ratio decreases. Besides, the results indicate that percentage increase in ventilation rate of opening ratio 4:1 and 2:1, 2:1 and 1:1, and 1:1 and 1:2 is higher than those of opening ratio for 1:2 and 4:9, 4:9 and 1:4. The study concluded that pairing a large outlet and small inlet leads to increase in better ventilation rate for building.